Decomposição dos diferenciais de rendimento do trabalho na região metropolitana de Curitiba e região não metropolitana do estado do Paraná - Maldaner, Iandra de Souza (2007)
The proposal in this study is of verifying the intra-regional dispersion of incomes of the busy people's main work in the Curitiba city Metropolitan Area (RMC) and No Metropolitan Area (RNM) Urban of the Paraná State, for Ronald Oaxaca's decomposition (1973) and through the data collected in the National Research by Sample of Home (PNAD) of 2004. The model bases on estimates of the wage function, for the groups to be considered, in the case of this study, RMC and RNM. In agreement with Mincer (1958 and 1974), the function wage of the human capital, relates the natural logarithm of the wage with the investment in human capital (years of study and experience), in other words, the human capital determines the income of the individual work according to the Human Capital Theory , it was still increased variables presented by the Theory of the Segmentation (section and activity branch). It is ended that there is intra-regional wages dispersion and that 58% of the salary dispersion are due to the workers' productive endowments and the market segmented intra-regional in the State. Already 42% of the dispersion are due to the wages prize that it serves as an amenity of the choice metropolitan locacional